Strategies To Drive Purchasing Decisions Through the Utilization Of Social Media - Ni Wayan Ekawati; Gede Suparna; Gede Bayu Rahanatha; Ni Made Intan Kusumasari; Dewa Ayu Agung Bunga Kinara PM (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
Applications that arise because of technological developments have the potential to change the consumer shopping experience through emerging social media. One of them is the use of augmented reality (AR) applications. As a relatively new application, it is important to examine its implementation in the MSME sector, related to positive response variables, purchasing decisions and stickiness variables as moderators. The research objectives are to test and explain the effect of augmented relality (AR) technology on purchasing decisions and positive responses, the effect of positive responses on purchasing decisions, as well as the role of positive responses mediating the relationship between AR and purchasing decisions, the role of stickiness as moderating the relationship between AR and purchasing decisions. The research was conducted in Denpasar Bali. This study used a sample of 400 respondents. The analysis technique used is path analysis technique. The research findings show that AR has a positive and significant effect on purchasing decisions and positive responses, positive responses have a positive and significant effect on purchasing decisions, positive responses do not play a mediating role, and stickiness plays a quasi-moderating role. Furthermore, these findings can be used as considerations by producers and marketers, to be able to face competition and develop business by utilizing information and communication technology. Meanwhile, the government is expected to be an input in making policies that encourage the pace of economic growth in Bali.